Periostin promotes migration and invasion of renal cell carcinoma through the integrin/focal adhesion kinase/c-Jun N-terminal kinase pathway - Sun Chuanyu; Zhu Yuqing; Xu Chong; Xia Guowei; Zhao Xiaojun (Tumor Biology)
Periostin (POSTN) is an extracellular matrix protein which is overexpressed in a variety of cancers and has been related to tumorigenesis of renal cell carcinoma. However, the involvement of POSTN in renal cell carcinoma migration, invasion, and their underlying mechanisms has not been established. In this study, renal cell carcinoma cell lines stably overexpressing POSTN were established using a lentiviral vector, and the effects of POSTN on renal cell carcinoma cell migration and invasion were investigated. POSTN overexpression increased the migration and invasion capabilities of renal cell carcinoma cell lines as well as activity of matrix metalloproteinase-2 and matrix metalloproteinase-9. Integrin α v β 3 and α v β 5 antibodies inhibited POSTN overexpression or recombinant POSTN-induced focal adhesion kinase activation, cell migration, and invasion. Furthermore, lentivirus-mediated focal adhesion kinase knockdown and c-Jun N-terminal kinase inhibitor reduced POSTN-enhanced phosphorylation of c-Jun N-terminal kinase, matrix metalloproteinase-9 and matrix metalloproteinase-2 expressions, cell migration, and invasion. Our research thus indicates that POSTN promotes renal cell carcinoma cell migration and invasion through interaction with integrins α v β 3 and α v β 5 and subsequent activation of the focal adhesion kinase/c-Jun N-terminal kinase pathway. These results suggest that POSTN plays a critical role in renal cell carcinoma metastasis and may represent a potential target for novel therapeutic approaches against renal cell carcinoma.